Graduate students and knowledge exchange with local stakeholders: possibilities and preparation - Duchelle, Amy E.; Biedenweg, K.; Lucas, C.; Virapongse, A.; Radachowsky, J.; Wojcik, D.J.; Londres, M.; Bartels, W.L.; Alvira, D.; Kainer, K.A. (2009)
Tropical biologists are exploring ways to expand their role as researchers through knowledge exchange with local stakeholders. Graduate students are well positioned for this broader role, particularly when supported by graduate programs. We ask: (1) how can graduate students effectively engage in knowledge exchange during their research; and (2) how can university programs prepare young scientists to take on this partnership role? We present a conceptual framework with three levels at which graduate students can exchange knowledge with stakeholders (information sharing, skill building, and knowledge generation) and discuss limitations of each. Examples of these strategies included disseminating preliminary research results to southern African villages, building research skills of Brazilian undergraduate students through semester-long internships, and jointly developing and implementing a forest ecology research and training program with one community in the Amazon estuary. Students chose strategies based on stakeholders' interests, research goals, and a realistic evaluation of student capacity and skill set. As strategies became more complex, time invested, skills mobilized, and strength of relationships between students and stakeholders increased. Graduate programs can prepare students for knowledge exchange with partners by developing specialized skills training, nurturing external networks, offering funding, maximizing strengths of universities in developed and developing regions through partnership, and evaluating knowledge exchange experiences. While balancing the needs of academia with those of stakeholders is challenging, the benefits of enhancing local scientific capacity and generating more locally relevant research for improved conservation may be worth the risks associated with implementing this type of graduate training model.